Efforts to address the Sustainable Development Goals in older populations: a scoping review - Vlada Shevelkova; Calum Mattocks; Louise Lafortune (BMC, 2023)
Abstract Background The United Nations Decade of Healthy Ageing (2021-2030) seeks to create multisectoral changes that align healthy ageing with the United Nations' Sustainable Development Goals (SDGs). Given that the SDGs have completed their first five years, the objective of this scoping review was to summarise any efforts launched to directly address the SDGs in older adults in community settings prior to the Decade. This will contribute to providing a baseline against which to track progress and identify gaps. Methods Following Cochrane guidelines for scoping reviews, searches were conducted in three electronic databases, five grey-literature websites, and one search engine between April to May 2021; and limited to entries from 2016 to 2020. Abstracts and full texts were double-screened; references of included papers were searched to identify additional candidate publications; and data were extracted independently by two authors, using an adaptation of existing frameworks. Quality assessment was not conducted. Results In total, we identified 617 peer-review papers, of which only two were included in the review. Grey literature searches generated 31 results, from which ten were included. Overall, the literature was sparse and heterogeneous, consisting of five reports, three policy documents, two non-systematic reviews, one city plan, and one policy appraisal. Initiatives targeting older adults were mentioned under 12 different SDGs, with SDG 1 (No Poverty), SDG 3 (Good Health and Wellbeing), SDG 10 (Reduced Inequalities), and SDG 11 (Sustainable Cities and Communities) being the most commonly discussed. Also, SDG-based efforts frequently overlapped or aligned to the eight domains of age-friendly environments outlined in the World Health Organisation framework. Conclusion The review has documented the extent, range, and nature of available research and provided an initial evidence backdrop for future research and policy development.